Study on the Characterization of Fillers and Different Rubber Crumb Ratio for Car’s Bumper - Yusoff, Numan; Norhasikin Ismail (Progress in Engineering Application and Technology, 2025)
This study investigates the development of sustainable composite materials using recycled rubber crumb and PVC pipe fillers for automotive bumper applications. Composites were prepared using epoxy resin and hardener, with rubber crumb incorporated at 20%, 40%, 60%, and 80% weight ratios to assess the influence on mechanical performance. Standardized mechanical tests were conducted in accordance with ASTM D638 (tensile), D790 (bending), and D6110 (impact). The 20% rubber crumb composition exhibited the highest tensile strength at 33.73 MPa and a maximum force of 1214 N, while the 40% composition demonstrated the best bending strength at 147.39 MPa. The 80% composition absorbed the highest impact energy at 0.13 J, indicating its suitability for applications requiring high energy absorption. These results highlight the potential for optimizing mechanical properties through tailored rubber crumb content. The 20% composition was identified as the most balanced option for bumper applications, offering strength, stiffness, and impact resistance. This work also promotes environmental sustainability by repurposing end-of-life tire materials into cost-effective, eco-friendly automotive components.